Modern Irish Literature and Society - Sub-Versions, 30.08.-03.09.2002., 6th ESSE Conference, Strasbourg, France - Gjurgjan, Ljiljana Ina (2002)
In the introduction to the panel, Gjurgjan has outlined its main concerns, namely the investigation of the operations of the postcolonial subversions in recounting the cultural master narratives.